Developing Simple Teaching Aids On Static Fluid Material As A Learning Media For Physics - Fathiah Alatas (Universitas Muhammadiyah Makassar, 2019)
The development of simple teaching aids in static fluid material is needed so that students better understand the concepts in the material. The concept that was initially considered abstract by students would be more concrete with the presence of teaching aids in the material, and the appropriate worksheets needed to be used as practical instructions. This study aims to determine: (1) the validity of the props developed; (2) practicality of props; (3) the effectiveness of teaching aids developed on student learning outcomes. The method used is the Research and Development (R D) method using the ADDIE model design. The trial subjects used 30 students of class XI MIA 1 MAN 3 Bogor. The results of the study show: (1) the validity of props is included in the valid category; (2) the practicality of props in terms of student responses shows very practical categories; (3) the effectiveness of teaching aids from student learning outcomes shows very effective categories with N-Gain values in the high category. These results indicate that the props developed have been used properly in the learning process.Keywords: teaching aids, learning media, static fluid.Pengembangan alat peraga sederhana pada materi fluida statis diperlukan agar siswa lebih memahami konsep pada materi tersebut. Konsep yang awalnya dianggap abstrak oleh siswa akan menjadi lebih kongkret dengan adanya alat peraga pada materi tersebut, serta LKPD yang tepat dibutuhkan untuk dijadikan sebagai petunjuk praktikum. Penelitian ini bertujuan untuk mengetahui: (1) validitas alat peraga yang dikembangkan; (2) kepraktisan alat peraga; (3) keefektifan alat peraga yang dikembangkan terhadap hasil belajar siswa. Metode yang digunakan adalah metode Research and Development (RD) dengan menggunakan desain model ADDIE. Sampel uji coba menggunakan 30 siswa kelas XI MIA 1 MAN 3 Bogor. Hasil penelitian menunjukkan: (1) validitas alat peraga termasuk dalam kategori valid; (2) kepraktisan alat peraga ditinjau dari respon siswa menunjukkan kategori sangat praktis; (3) efektivitas alat peraga dari hasil belajar siswa menunjukkan kategori sangat efektif dengan nilai N-Gain berada pada kategori tinggi. Hasil tersebut menunjukkan bahwa alat peraga yang dikembangkan telah layak digunakan dalam proses pembelajaran.Kata kunci: alat peraga, media pembelajaran, fluida statis.